Correlation between Hospital Volume of Severely Injured Patients and In-Hospital Mortality of Severely Injured Pediatric Patients in Japan: A Nationwide 5-Year Retrospective Study - Toida, Chiaki (J Clin Med, 2021)
Appropriate trauma care systems, suitable for children are needed; thus, this retrospective nationwide study evaluated the correlation between the annual total hospital volume of severely injured patients and in-hospital mortality of severely injured pediatric patients (SIPP) and compared clinical parameters and outcomes per hospital between low- and high-volume hospitals. During the five-year study period, we enrolled 53,088 severely injured patients (Injury Severity Score, ≥16); 2889 (5.4%) were pediatric patients aged <18 years. Significant Spearman correlation analysis was observed between numbers of total patients and SIPP per hospital (p < 0.001), and the number of SIPP per hospital who underwent interhospital transportation and/or urgent treatment was correlated with the total number of severely injured patients per hospital. Actual in-hospital mortality, per hospital, of SIPP patients was significantly correlated with the total number patients per hospital (p < 0.001,). The total number of SIPP, requiring urgent treatment, was higher in the high-volume than in the low-volume hospital group. No significant differences in actual in-hospital morality (p = 0.246, 2.13 (0–8.33) vs. 0 (0–100)) and standardized mortality ratio (SMR) values (p = 0.244, 0.31 (0–0.79) vs. 0 (0–4.87)) were observed between the two groups; however, the 13 high-volume hospitals had an SMR of <1.0. Centralizing severely injured patients, regardless of age, to a higher volume hospital might contribute to survival benefits of SIPP.